The Limitation of the Ecotourism Development with The Participation of Community by the Context of Law - เบญจวรรณ, ธันวา; สมทรัพย์, ชุติพงศ์ (Ganesha Journal, 2018)
Ecotourism is a form of sustainable tourism. It is a visiting of natural destination to learn history and culture with caution, not to cause any ecological damage. The ecotourism also enhances the economic opportunities that result in the conservation of natural resources to benefit the local. The major characteristic of ecotourism is a Nature-based Tourism that linked to the history, art, culture, and way of life of local people in the natural ecosystem. Moreover, the ecotourism does not affect the natural and cultural pathways that cause any negative changes. Even though, the management of ecotourism in Thailand tries to balance between two objectives, conservation of natural resources and tourism, but the management of natural resources conservation by the law mainly has the prohibitive and enforced context, and the tourism management has no law that requires the participation of local communities. The law that allows the local communities to participate in only such role in activities of ecotourism leads to result in the lack of the value of nature and ecology awareness, as well as the lack of knowledge and understanding of the appropriate tourism management models of the economic returns and the good quality of life. The essential legislations that directly affect the management of ecotourism in natural resources that include the National Park Act, the National Forest Act, the Forest Act, the Wildlife Conservation Act and the Wildlife Protection Act, are the main laws that govern the tourism development. The interesting facts are the conflicts of the related legislations that are not conducive to the ecotourism development, have contradictions of the guilt and penalty, and have contradictions to the way of life of the local communities, and have the ineffective law enforcement as well. The guidelines for reducing the limitations of the legal context that has a direct impact on the management of ecotourism in Thailand are adjusting the overlapping of the forest areas and the national park areas with local community participation, enforcing the related law strictly and clearly, and raising the awareness of the conservation of natural resources and the participation of the public sector.